Quantification of Infarct Core Volume in Patients with Acute Ischemic Stroke Using Cerebral Metabolic Rate of Oxygen in CT Perfusion - Otgonbaatar, Chuluunbaatar; Song, Huijin; Jung, Keun-Hwa; Hwang, Inpyeong; Hun Jeon, Young; Choi, Kyu Sung; Yoo, Dong Hyun; Sohn, Chul-Ho (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: The cerebral metabolic rate of oxygen (CMRO2) is considered a robust marker of the infarct core in 15O-tracer–based PET. We aimed to delineate the infarct core in patients with acute ischemic stroke by using commonly used relative CBF (rCBF) < 30% and oxygen metabolism parameter of CMRO2 on CT perfusion in comparison with pretreatment DWI-derived infarct core volume.MATERIALS AND METHODS: Patients with acute ischemic stroke who met the inclusion criteria were recruited. The CMRO2 and CBF maps in CT perfusion were automatically generated by using postprocessing software. The infarct core volume was quantified with relative cerebral metabolic rate of oxygen (rCMRO2) <20% –30% and rCBF <30%. The optimal threshold was defined as those that demonstrated the smallest mean absolute error, lowest mean infarct core volume difference, narrowest 95% limit of agreement, and largest intraclass correlation coefficient (ICC) against the DWI.RESULTS: This study included 76 patients (mean age ± standard deviation, 69.97 ± 12.15 years, 43 men). The optimal thresholds of rCMRO2 <26% resulted in the lowest mean infarct core volume difference, narrowest 95% limit of agreement, and largest ICC among different thresholds. Bland-Altman analysis demonstrated a volumetric bias of 1.96 mL between DWI and rCMRO2 <26%, whereas in cases of DWI and rCBF <30%, the bias was notably larger at 14.10 mL. The highest correlation was observed for rCMRO2 <26% (ICC = 0.936), whereas rCBF <30% showed a slightly lower ICC of 0.934.CONCLUSIONS: CT perfusion–derived CMRO2 is a promising parameter for estimating the infarct core volume in patients with acute ischemic stroke.CMRO2cerebral metabolic rate of oxygenICCintraclass correlation coefficientOEFoxygen extraction fractionrCBFrelative CBFrCMRO2relative cerebral metabolic rate of oxygen